Analisis Faktor-Faktor Yang Mempengaruhi Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia - Pratiwi, Prisma Laras; Nurhayati, Ida (SEIKO : Journal of Management & Business, 2023)
Abstract This study aims to examine and analyze the effect of Economic Value Added, Market Value Added, Return On Equity, Earning Per Share, Debt to Equity Ratio on stock prices. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021. The number of samples used is 240 observational data. The sampling technique used purposive sampling. The data used is secondary data, with data collection using documentation in the form of financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The analytical tool used is multiple regression, while to test the hypothesis using the t test. The results showed that the results of the hypothesis test showed that Economic Value Added had a significant effect on stock prices, Market Value Added had a significant effect on stock prices, Return On Equity had a significant effect on stock prices, Earning Per Share had a significant effect on stock prices, and Debt to Equity Ratio no significant effect on stock prices. Keywords: Economic Value Added, Market Value Added, Return On Equity, Earning Per Share, Debt to Equity Ratio, and Stock Price. Abstrak Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh Economic Value Added,nMarket Value Added, Return On Equity, Earning Per Share, Debt to Equity Ratio terhadap harga saham. Populasi yang digunakan pada penelitian ini yaitu perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2019 sampai 2021. Jumlah sampel yang digunakan sebesar 240 data pengamatan. Teknik pengambilan sampel menggunakan purposive sampling. Data yang digunakan adalah data sekunder, dengan pengumpulan data menggunakan dokumentasi berupa laporan keuangan perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia. Alat analisis yang digunakan regresi berganda, adapun untuk menguji hipotesis menggunakan uji t. Hasil penelitian menunjukkan dari hasil uji hipotesis diperoleh bahwa Economic Value Added berpengaruh signifikan terhadap harga saham,nMarket Value Added berpengaruh signifikan terhadap harga saham, Return On Equity berpengaruh signifikan terhadap harga saham, Earning Per Share berpengaruh signifikan terhadap harga saham, dan Debt to Equity Ratio tidak berpengaruh signifikan terhadap harga saham. Kata Kunci : Economic Value Added,nMarket Value Added, Return On Equity, Earning Per Share, Debt to Equity Ratio, dan Harga Saham.